Feeding Value Of Rubber Seed Meal For Laying Hens - Amritha Vally Panan (Department of Poultry Sciences, College of Veterinary and Animal Sciences, 1977)
An investigation was carried out to study the feeding value of rubber seed meal for layers in view to its exploitation as a newer unconventional protein source for poultry. Thirty-six, S.C. White Leghorn pullets aged 20 weeks were housed in individual cages on four dietary regimes. One group was fed a basal diet containing groundnut cake as the vegetable protein source and formed control, while the other groups were fed experimental diets containing rubber seed meal at 10, 15 and 20 per cent levels partially replacing ground nut cake. Major economic characters like hen-day egg production, feed consumption, feed efficiency, body weight maintenance, egg weight, egg quality and livability were studied for five, 28-day periods. The results obtained during the course of investigation are presented and discussed. Incorporation of rubber seed meal at 10 per cent was found to be superior as far as hen-day egg production and feed intake were concerned. Feed efficiency and body weight maintenance were not significantly affected by different dietary treatments. Egg weight was significantly depressed among birds fed rubber seed meal in their diets. Per cent yolk and per cent albumen showed no change attributable to treatments. However the per cent shell increased in rubber seed meal fed groups. The group fed with 10 per cent rubber seed meal in the diet excelled the other three groups based on the overall performance, while, the feed cost per unit production favoured the 15 per cent rubber seed meal fed group. Laying house mortality was not at all influenced by feeding rubber seed meal. It was concluded that inclusion of rubber seed meal as a protein concentrate in layer diet is useful upto 15 per cent level. However, its adverse effect on egg size has been pointed out as a probable drawback.